2007
DOI: 10.1038/sj.jp.7211760
|View full text |Cite
|
Sign up to set email alerts
|

Congenital ovarian cyst

Abstract: Case presentationFetal ovarian cysts were first described as a prenatal finding by Valenti et al. 1 in 1975 and were believed to be a rare finding. 1 With recent technologic advancements in prenatal sonography, fetal ovarian cysts have been detected more frequently. Ovarian and genital tract abnormalities constitute approximately 20% of all abdominal masses in the neonate.These cysts vary in size; they can be simple or complex, and are commonly unilateral. Intrauterine complications such as torsion and ruptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The most common complication to arise in congenital ovarian cyst is development of torsion of the ovarian pedicle which forms 50 to 70% of all complications. [4,5] The remaining complications being haemorrhage, rupture, peritionitis secondary to inflammation, urinary tract obstruction, bowel obstruction, autoamputation and in rare case of sterile necrosis of the ovary. These congenital ovarian cysts are known to undergo spontaneous regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common complication to arise in congenital ovarian cyst is development of torsion of the ovarian pedicle which forms 50 to 70% of all complications. [4,5] The remaining complications being haemorrhage, rupture, peritionitis secondary to inflammation, urinary tract obstruction, bowel obstruction, autoamputation and in rare case of sterile necrosis of the ovary. These congenital ovarian cysts are known to undergo spontaneous regression.…”
Section: Discussionmentioning
confidence: 99%
“…Such predictive markers on prenatal USG include length of the ovarian pedicle, size of the cyst, laxity of the ovarian and infundibular ligament, solitary or multiple cyst in the same ovary, unilateral or bilateral involvement, simple versus complex nature of cyst, presence /absence of increased vascularity or congestion of ovarian pedicle on colour doppler. [5] Torsion of ovarian pedicle does result in inflammatory process reflected by subtle rise in alpha foeto protein/carcinoembryonic antigen levels but they have not been found to be predictive in identifying development of complications in congenital ovarian cysts. The most important markers on prenatal ultrasonogram to predict a complication include size and eco pattern of the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Literature survey revealed NOC also occurs in healthy mothers often. 11 Though serous cystadenomas constitute approximately 40% of all ovarian tumors occurring in the reproductive age group, 12 it is infrequent in the fetus. From the literature search, only three studies [3][4][5] have reported serous cystadenoma among the NOC.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of CACL has risen dramatically with extended use of ultrasound examination (5). Furthermore, nowadays, the quality of available sonographic devices is much better; growing expertise allows for near-exact qualification of cystic lesions in terms of both origin and localization.…”
Section: Discussionmentioning
confidence: 99%